Дослідження коефіцієнтів зведення у щільних транспортних потоках - Форнальчик, Є. Ю.; Леськів, І. О.; Леськів, М. О. (Видавництво Львівської політехніки, 2013)
The necessity of usage of passenger car unit equivalent for destiny traffic flows is shown. Vehicles were classified on passenger cars, trucks and buses. It is determined that values of passenger car unit equivalents are smaller for all vehicle types than given in regulatory documents. The usage of theirs will allow take into account traffic flow composition at urban street network more adequately.
Keywords: транспортні засоби; щільні транспортні потоки; часовий інтервал; склад транспортного потоку; коефіцієнти зведення